Effects of Ergonomics Education on Knowledge, Dental Practice, and Musculoskeletal Disorders of Dental Personnel at the Institute of Dentistry - Pongwatcharaporn, Mayuree; Kessuwanrak, Rassami (Journal of The Department of Medical Services, 2022)
Background: Dentists’ career is at high risk of developing musculoskeletal disorders. The symptoms may bemild or so severe that they affect the ability to work. Therefore, ergonomics education is necessary to prevent thosesymptoms. Objective: The objective of this research was to compare the mean score of knowledge, practice, andpain before and after receiving ergonomics education. Methods: This was quasi-experimental research. Data werecollected by conducting self-responding sample-type questionnaires. The questionnaire consisted of four sections:general information and health information, information about the dental working position and daily behavior,musculoskeletal pain symptoms and solutions, and a quiz measuring the knowledge of ergonomics. The samplegroup was dental personnel at the Institution of Dentistry: 50 dentists and 30 dental assistants. When the samplegroup had completed the questionnaires, they received leaflets advising about the ergonomic working position andstretching exercises. The data were collected again in the following month using the original questionnaire. Thestatistical data were then analyzed using the pair t-test and Wilcoxon Signed Rank test at 95%CI. Results: The resultsshowed that after receiving ergonomics education, the dentist’s group had a statistically significantly higher meanscore of knowledge and working posture than before receiving the education, whereas the dental assistants’ group’sresult was not different. However, both groups had the same mean score regarding the frequency and intensity ofpain before and after receiving ergonomics education. Conclusion: In the dentist’s group, ergonomics educationresults in increased knowledge of ergonomics and better practice in dental work; however, it does not affect thefrequency and severity of musculoskeletal disorders. We have also found that dentists had a statistically significantincrease in their knowledge of proper working postures. On the other hand, in the group of dental assistants, theergonomics education has not increased knowledge, practice in dental work, or the frequency and severity ofmusculoskeletal disorders.